The Potentials of Antioxidant Micronutrients in the Management of Metabolic Syndrome - L.S. Bilbis; S.A. Muhammad; Y. Saidu (Journal of Antioxidant Activity, 2014)
There is increasing evidence of the prevalence manifestations of metabolic syndrome worldwide. Metabolic syndrome is a cluster of abnormalities characterized by hypertension, central obesity, insulin resistance, endothelial dysfunction, dyslipidemia and oxidative stress. All these alterations predispose individuals to type 2 diabetes and cardiovascular disease that are major contributing factors to earlier mortality among people. The investigation of food nutrients that could reverse the features of metabolic syndrome is an important aspect for dietary-based therapies that may ameliorate the burden of the disorder. Antioxidant micronutrients are of great interest due to the recent described association between obesity, cardiovascular alterations and oxidative stress. These antioxidant nutrients are also being considered in the management of metabolic syndrome due to their potential benefits on hypertension, insulin resistance and hypertriglyceridemia since growing evidence has emerged that point to a causal link between oxidative stress and metabolic syndrome. Thus, dietary antioxidant supplements could have favourable effect on the attenuation and prevention of the manifestations of metabolic syndrome traits. Therefore, the present review focuses on the importance of antioxidant micronutrients in the treatment and management of metabolic syndrome.
Keywords: Metabolic syndrome